Right breast cancer with contralateral left axillary sentinel lymph node detected through lymphoscintigraphy - Salem, Yousif; Alkhaja, Sara; Alshaibani, Noof; El Gaid, Salwa Abd (International Surgery Journal, 2019)
Altered contralateral axillary drainage is extremely rare after curative breast cancer treatment. We present a case of a 64 year-old women, with a past history of right breast invasive ductal carcinoma managed surgically by lumpectomy and right axillary lymph node dissection 20 years ago. She presented with recurrent right breast cancer and was scheduled to undergo right mastectomy along with sentinel lymph node biopsy. Technetium-99m nano colloid sentinel lymphoscintigraphy performed on the day of surgery showed sentinel lymph node on the contralateral left axilla. This case report aims to discuss the presentation of such uncommon contralateral sentinel axillary lymph nodes in patients with breast cancer and highlight the importance of considering the lymphatic obliteration after ipsilateral axillary lymph node clearance.